European Economy / Economic Transformation in Hungary and Poland: No 43 - Directorate For Economic And Financial Affairs; European Commission (1990)
Reports prepared by a group of independent experts. Preface, List of Experts, Introduction by R. Portes, Papers on Hungary, Papers on Poland, Paper Common to Both Countries.